Pharmacophore Modeling, Ensemble Docking, Virtual Screening, and Biological Evaluation on Glycogen Synthase Kinase‐3β. Issue 9 (2nd September 2014) - Fu, Gang; Sivaprakasam, Prasanna; Dale, Olivia R.; Manly, Susan P.; Cutler, Stephen J.; Doerksen, Robert J.
Abstract Glycogen synthase kinase‐3 (GSK‐3) is a multifunctional serine/threonine protein kinase which is engaged in a variety of signaling pathways, regulating a wide range of cellular processes. GSK‐3β, also known as tau protein kinase I (TPK‐I), is one of the most important kinases implicated in the hyperphosphorylation of tau that leads to neurodegenerative diseases. Hence, GSK‐3β has emerged as an important therapeutic target. To identify compounds that are structurally novel and diverse compared to previously reported ATP‐competitive GSK‐3β inhibitors, we performed virtual screening by implementing a mixed ligand/structure‐based approach, which included pharmacophore modeling, diversity analysis, and ensemble docking. The sensitivities of different docking protocols to induced‐fit effects were explored. An enrichment study was employed to verify the robustness of ensemble docking, using 13 X‐ray structures of GSK‐3β, compared to individual docking in terms of retrieving active compounds from a decoy dataset. A total of 24 structurally diverse compounds obtained from the virtual screening underwent biological validation. The bioassay results showed that 15 out of the 24 hit compounds are indeed GSK‐3β inhibitors, and among them, one compound exhibiting sub‐micromolar inhibitory activity is a reasonable starting point for further optimization.